Optimizing Phosphatic Fertilizer Drip Timing to Improve Cotton Yield in Saline–Alkali Soil and Mitigate Phosphorus–Calcium Binding Risks - Xiangxi Bu; Xiangwen Xie; Changxue Wu; Manqi Liu; Yongmei Xu (Agronomy)
To improve cotton yield in salinized arid fields, excess salt is removed and phosphorus content is increased. Adjusting phosphate fertilizer timing with water and fertilizer reduces phosphorus binding with calcium ions. Salt removal precedes phosphate application, enhancing soil phosphorus availability and promoting better growth. However, the optimal time for delaying phosphate fertilizer drip irrigation remains unclear. Therefore, this study evaluated the total salt, soil available phosphorus, and cotton yield under the condition of delayed phosphate fertilizer application. We conducted a field experiment using a completely randomized design to adjust the timing of phosphatic fertilizer application and apply the same amount of pure phosphorus. Specifically, “t” was defined as the total duration of one irrigation cycle, and the starting points for phosphorus application were as follows: T1, 1 h; T2, 1 h + 1/3 t h; T3, 1 h + 2/3 t h; CK, 1/3 t h. These values represent the duration of salt leaching through irrigation in each treatment. Phosphate fertilizer was applied to the soil after salt washing was complete. The results revealed that the T2 treatment exhibited the highest SPAD value (64.53), which was 11.46% and 15.48% higher than that of the T1 and T3 treatments. The 0–20 and 20–40 cm soil layers under the T2 treatment had the highest pH values of 9.12 and 9.37, representing increases of 1.93%, 1.21%, 4.50%, and 1.38% compared with T1 and T3 treatments, respectively (p < 0.05). At the bud stage, the Olsen-P in the T2 treatment was 82.86% and 26.53% higher than that in the T1 and T3 treatments, respectively (p < 0.05). The T2 treatment achieved the highest yield of 6492.09 kg/hm2, which was 31.47%, 31.53%, and 2.77% higher than that of T1, T3, and CK. Overall, the T2 treatment increased cotton yield and reduced the adsorption of calcium ions to available phosphorus in salinized soil. This study provides an effective technical approach for the sustainable development of salinized cotton fields in Xinjiang.